Binding mode analysis of dual inhibitors of human thymidylate synthase and dihydrofolate reductase as antitumour agents via molecular docking and DFT studies - Arooj, Mahreen; Lee, K. (Taylor and Francis Ltd., 2015)
Due to the diligence of inherent redundancy and robustness in many biological networks and pathways, multitarget inhibitors present a new prospect in the pharmaceutical industry for treatment of complex diseases. Nevertheless, to design multitarget inhibitors is concurrently a great challenge for medicinal chemists. Human thymidylate synthase (hTS) and human dihydrofolate reductase (hDHFR) are the key enzymes in folate metabolic pathway that is necessary for the biosynthesis of RNA, DNA and protein. Their inhibition has found clinical utility as antitumour, antimicrobial and antiprotozoal agents. The aim of this study is to elucidate the factors which are responsible for the potent inhibition of hTS and hDHFR, respectively, through the detailed analysis of the binding modes of dual TS-DHFR inhibitors at both active sites using molecular docking study. Moreover, this study is also accompanied by the exploration of electronic features of dual inhibitors via the density functional theory approach. This study demonstrates that appropriate substitution at the sixth position of thieno[2,3-d]pyrimidines moiety in non-classical dual inhibitors of hTS and hDHFR plays a key role in the inhibition of hTS and hDHFR enzymes. In general, the outcomes of this research exertion will significantly be helpful in drug design for cancer chemotherapy.